O jogo com a cena documentária: um estudo do filme Jogo de Cena, de Eduardo Coutinho - Ursula de Almeida Rosele (2011)
In this dissertation we chose a specific subject between the several possibilities in stylistic, narratives and self-reflective approaches on the contemporary documentary scenario. From the movie Jogo de Cena (2007), of Eduardo Coutinho, we tried to investigate how each female character develops its performance and how this was articulated by the directors mise-en-scène and devices inside a theater space.